NILAI KEARIFAN UPACARA TRADISIONAL SUSUK WANGAN SEBAGAI BENTUK SOLIDARITAS SOSIAL DAN PELESTARIAN LINGKUNGAN DI DESA SETREN KECAMATAN SLOGOHIMO KABUPATEN WONOGIRI - Wiganingrum, Anditya (Candi, 2013)
ABSTRACK The aims of this study is to describe: (1) background of susuk wangan traditional ceremony appearance, (2) the procession of susuk wangan traditional ceremony, (3) wisdom value that implied in traditional ceremony of susuk wangan. Based on the results of research can be concluded: (1) village society wisdom Setren in watch over environment passes traditional ceremony of susuk wangan is Setren society mechanism in watch over forest and spring source with attach forest with myth trusted Setren society. Traditional ceremony of susuk wangan as a grateful for God who have given water that overlow and fertile soil (2) traditional ceremony of susuk wangan contains symbolic meaning in ceremony equipment and symbolic behavior of ceremony executans (3) traditional ceremony of susuk wangan keeps various moral value that delivered nonverbal as human with the God. This ceremony contains social solidarity value and environment presevation that respected by the supporter society (4) as social solidarity and appear environment by didn?t cut down the forest illegally, clean spring source, clean the water land wangan with flow trugh Setren village. Keywords: local wisdom, traditional ceremony, susuk wangan, social solidarity, environment preservation.